Challenging anticoagulation cases: Cancer-associated venous thromboembolism and chemotherapy-induced thrombocytopenia – A case-based review of clinical management. Issue 199 (March 2021) - Moik, Florian; Makatsariya, Alexander; Ay, Cihan
Abstract: Patients with cancer undergoing chemotherapy are at risk of thrombocytopenia. The co-incidence of cancer-associated venous thromboembolism (VTE) and thrombocytopenia is a frequent complication in patients with cancer. Especially in certain tumour entities at high VTE risk, chemotherapeutic agents with myelosuppressive effects are part of the standard of care. The management of cancer-associated VTE in the setting of chemotherapy-induced thrombocytopenia is challenging, in the absence of evidence from high-quality studies. Thrombocytopenia is associated with both increased risk of recurrent VTE and risk of bleeding during anticoagulation. In this case-based concise review, we aimed at summarizing available literature and expert consensus guidance on the treatment of cancer-associated VTE in patients with chemotherapy-induced thrombocytopenia. Highlights: Patients with cancer are at risk for thrombocytopenia and venous thromboembolism (VTE). High risk of VTE recurrence & bleeding during anticoagulation with thrombocytopenia Anticoagulation needs to be based on platelet count and individual VTE risk profile.